ANALISIS KONSEP AKUNTANSI SYARIAH TERHADAP METODE PENGAKUAN PENDAPATAN PADA PT. BANK SULSELBAR SYARIAH CABANG MAKASSAR - fadillah, andi siti; Khalid, Idham (Universitas Muhammadiyah Makassar, 2019)
The results of the study show that the noble purpose of shari'a creates benefit is the main reference in the formulation of the principles of shari'ah accounting, and the fruits of syari'ah accounting are its financial statements. If then this report is used as the basis for business transactions, accountability will be very well maintained. If the principles of shari'ah accounting can be adopted in presenting financial statements, of course the hope is to maintain the existence of financial statements so that they can still be used as the main reference in making business decisions. Descriptions of the performance of a bank both general and shari'ah are usually reflected in reports in the report the finance. The financial statements aim to provide useful information for interested parties in economic capture. From the results of the study, it can be concluded that at PT. Bank Sulselbar Syariah Makassar Branch in the recording process uses the cash basis method, where revenue is recognized when the income is received.